Projeto rede de apoio social: transformando sofrimento em competência - Costa, Celoi Araujo dos Santos (2009)
This study has the aim at verifying the impact of social support network project in families which receive Bolsa Família programme. Therefore it is important to consider the economic background of our current society, as well as the challenges for the municipalities in the creation of alternatives and deployment of public policies to include the most disadvantaged citizens economically. Thereafter, we describe the target of this research into contextualizing Projeto Rede de Apoio Social, as well as the implementation of it in Balneário Pinhal town. The theoretical research focuses on: Family, poverty, Bolsa Família programme, community therapy, resiliency, ethics, social networks and care, establishing a relation between the theoretical framework and the guiding study carried out. Afterwards the instruments that have been used in data collection are defined. Through the results obtained by the research we believe that it is possible to analyse the impact of Rede de Apoio Social Project, not only among the beneficiaries of Bolsa Família programme, but in the community as a whole, including municipal authorities. Through this, we intend to reaffirm the importance of the implementation of public policies that support iniciatives that make possible alternatives of income as well the civil society organization in order to benefit the independence